The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.17576/jsm-2021-5005-23
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Antioxidant Activity of Malaysian Ginger (Zingiber officinale Roscoe) Extracts with that of Selected Natural Products and its Effect on the Viability of Myoblast Cells in Culture

Abstract: Ginger has been proven to possess various therapeutic effects, including antibacterial, anticancer, anti-inflammatory, and antioxidant effects. However, data on the comparison of ginger antioxidant activity with that of other natural products are still lacking. This study aimed to analyse and compare the antioxidant properties of two types of Malaysian ginger extracts (GE1 and GE2) with that of selected natural products. The antioxidant activities were measured by 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This increased antioxidant power can be due to the soil ginger’s higher yield of total [6]-gingerols and [6]-shogaols, which resulted in a higher presence of total α, and β-unsaturated ketones moieties than in soilless ginger. In comparison to Moringa oleifera , Kelulut honey ( Mohd Sahardi et al, 2021 ), and other spices extracts ( Abdul Qadir et al, 2017 ), ginger showed stronger antioxidant activity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This increased antioxidant power can be due to the soil ginger’s higher yield of total [6]-gingerols and [6]-shogaols, which resulted in a higher presence of total α, and β-unsaturated ketones moieties than in soilless ginger. In comparison to Moringa oleifera , Kelulut honey ( Mohd Sahardi et al, 2021 ), and other spices extracts ( Abdul Qadir et al, 2017 ), ginger showed stronger antioxidant activity.…”
Section: Discussionmentioning
confidence: 97%
“…The organic nitrogen free radical known as the DPPH free radical has a deep purple colour which turned yellow during the test. Antioxidants contained in the ginger extract donate hydrogen in order to scavenge the DPPH free radical in the DPPH assay, which helped to create the non-radical form of DPPH ( Mohd Sahardi et al, 2021 ). In FRAP assay, the identified antioxidant property changed the ferrous ion (Fe 2+ ) from the ferric ion (Fe 3+ ), causing a blue complex (Fe 2+ /TPTZ) to form ( Spiegel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different ages of cells were treated with various dosages of ginger extract. Young cells (PD14) were treated with 0, 50, 200 µg/mL ginger extract, pre-senescent cells (PD 18) at 0, 50, 300 µg/mL and senescent cells (PD 21) at 0, 100, 300 µg/mL These dosages were chosen based on the result of a cell viability assay from our previous study [26].…”
Section: Ginger (Zingiber Officinale Roscoe) Extract Preparation and ...mentioning
confidence: 99%